2011
DOI: 10.4103/0256-4947.78204
|View full text |Cite
|
Sign up to set email alerts
|

Urine iodine excretion ın patients with euthyroid noduler disease

Abstract: BACKGROUND AND OBJECTIVES:Different nutritional and environmental factors are responsible for the pathogenesis of goiter, but iodine deficiency is the most important factor. However, little is known about the natural course of benign thyroid nodules in euthyroid patients over time. Few studies have used ultrasonographic evaluation to address this issue, especially in iodine-deficient areas. In this study, we present the long-term follow-up of benign thyroid nodules in a iodine-deficient area.DESIGN AND SETTING… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In recent studies, thyroid volume (TV) has been found to be associated with age, anthropometry, smoking, iodine status and hyperinsulinemia [5-8]. Additionally, growth hormone and growth factors such as insulin like growth factor, epidermal growth factor have been shown to affect TV [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, thyroid volume (TV) has been found to be associated with age, anthropometry, smoking, iodine status and hyperinsulinemia [5-8]. Additionally, growth hormone and growth factors such as insulin like growth factor, epidermal growth factor have been shown to affect TV [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the association between UIC and thyroid diseases 15 , 16 and thyroid cancer 17 19 , but to our knowledge, well-designed epidemiologic studies on the association between UIC and the risk of thyroid cancer are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor: In the September–October/2011 issue of your journal I commented 1 on the article by Cakir and colleagues on urinary iodine excretion in patients with euthyroid nodular disease. 2 I am glad that Cakir responded to my concerns. 3 Cakir made the point that there are controversies about the cut-off values on urinary iodine excretion and that measurement of iodine levels in spot urine sample is found to be as sensitive as other screening modalities.…”
mentioning
confidence: 98%
“…Second, Cakir and colleagues started their original study 2 with three groups significantly different in the proportions of smokers and those with additional diseases. Any difference in outcome after one year of follow up could be attributed to one of these two variables.…”
mentioning
confidence: 99%